1976
DOI: 10.1136/thx.31.6.660
|View full text |Cite
|
Sign up to set email alerts
|

Sarcoidosis of the upper respiratory tract and its association with lupus pernio.

Abstract: . (1976). Thorax, 31,[660][661][662][663][664]. Sarcoidosis of the upper respiratory tract and its association with lupus pernio. In a series of 34 patients with sarcoidosis affecting the upper respiratory tract and nose, 26 had lupus pernio (LP) and 17 had sarcoidosis of the upper respiratory tract (SURT). In nine patients these features coexisted. A patient presenting with SURT carried a 50% risk of developing LP although one feature could be present without the other. Both were disorders of women of the chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
37
0

Year Published

1978
1978
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(39 citation statements)
references
References 13 publications
2
37
0
Order By: Relevance
“…Nasal sarcoidosis commonly affects the mucosa of the inferior turbinates and the septum and, sometimes [5], that of the paranasal sinuses, although they are rarely involved without any macroscopic changes in the nasal mucosa [4]. Maybe, paranasal sarcoidosis may be underestimated in patients with systemic sarcoidosis for an inaccurate management [7]. Therefore, we report an interesting lupus pernio case with histological demonstration of extensive involvement of a maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal sarcoidosis commonly affects the mucosa of the inferior turbinates and the septum and, sometimes [5], that of the paranasal sinuses, although they are rarely involved without any macroscopic changes in the nasal mucosa [4]. Maybe, paranasal sarcoidosis may be underestimated in patients with systemic sarcoidosis for an inaccurate management [7]. Therefore, we report an interesting lupus pernio case with histological demonstration of extensive involvement of a maxillary sinus.…”
Section: Discussionmentioning
confidence: 99%
“…The lesions on the tip of the nose cause a bulbous appearance. The nasal mucosa is usually involved [7], and underlying bone can be destroyed. On the other hand, it is rare for sarcoidosis to affect the nose exclusively.…”
Section: Discussionmentioning
confidence: 99%
“…Lupus pernio describes a form of sarcoidosis with violaceous plaques on the central face [1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11]. It was first described by Ernest Besnier in 1889 [12].…”
Section: Discussionmentioning
confidence: 99%
“…It is a violaceous, indurated plaque that is characteristically located on the nose, ears, lips and other areas of the face. Typically seen in women, lupus pernio is associated with chronic, persistent sarcoidosis that has a predilection for upper respiratory involvement [1, 2, 3, 4, 5, 6, 7, 8, 9, 10]. However, frank cutaneous tumors are rarely seen in lupus pernio.…”
Section: Introductionmentioning
confidence: 99%
“…The poorer prognosis associated with cutaneous sarcoidal granulomas drawn from populations with proved systemic sarcoidosis does not seem to apply to generally healthy outpatients with skin lesions as the initial manifestation of their disease. (Arch Dermatol 1981;117:203-207) Cutaneous sarcoidal granulomas are reported to occur in 10% to 35% of patients with systemic sarcoidosis.1" Extensive reviews of patients with systemic sarcoidosis have indicated that the presence of cutaneous sarcoidal granulomas portends a graver prognosis with the more frequent occurrence of pulmonary fibrosis and uveitis.36- 9 We studied patients who had asymptomatic skin lesions that, on biopsy, showed typical changes consistent with cutaneous sarcoidosis. It was our impression that cuta¬ neous sarcoidal granulomas frequently occurred in the absence of other subjective and objective evidence of systemic sarcoidosis.…”
mentioning
confidence: 99%